Three essays on corporate finance - Zhang, Quan (Nanyang Technological University, 2023)
My thesis covers three critical aspects of corporate finance, including the initial return of an initial public offering, the impact of employment protection on municipal financing, and the risk-mitigating benefit of passive institutional investors. In Chapter 1, we examine whether the presence of a minority CEO affects a firm’s IPO outcomes. We find a stylized fact that minority-helmed companies experience higher initial returns, upward price revisions, and post-IPO stock return volatility. Excessive IPO underpricing with minority CEOs can attract subscription from heterogeneous investors and correspond to the uncertainty surrounding the valuation of firms. The evidence in this paper conforms with the uncertainty models and book building models of IPO underpricing. The higher cost for going public, however, is not associated with the difference in post-IPO firm performance and auxiliary services. In Chapter 2, I exploit the adoption of U.S. state-level employment protection laws to examine whether employment protection affects municipal bond financing. I find that employment protection raises the issuance yield of municipal bonds. The results are more evident when the state unemployment rate is high, when bonds are callable, and when bonds are issued in high tax privilege states. While the bond issuance cost increases, employment protection benefits the credit rating of municipalities. In state-level analysis, I find a marginal decrease in governments’ municipal bond issuance and significant increase in public safety expenditure with the adoption of employment protection laws, suggesting that state governments support incumbent employees with more spending and financing. Chapter 3 investigates the effect of passive institutional shareholders on loan contract terms. Banks charge lower loan spreads and require less collateral for firms with higher passive institutional ownership. Moreover, the lead arranger of syndication holds less loan portion of firms with higher passive institutional ownership. The results are attenuated when firms are larger, have more analyst following, and pay higher dividends. The results are robust to using alternative measures of passive institution ownership. The results are also robust to using annual Russell Index reconstitutions as an exogenous shock to passive institutional ownerships. The results suggest that the monitoring role of passive institutional investors is beneficial for debtholders.